The dissipation of marital assets pending a divorce order in South Africa: a proposal for reform - Mahlangu, Busisiwe Hlophane Maria (Rhodes University, Faculty of Law, Law)
Dissipation of marital assets takes place where one spouses uses the marital assets with the intention to frustrate the equitable distribution at the dissolution of marriage. This kind of behaviour usually occurs when one spouse anticipates a divorce or when the final divorce order is pending. In this context then, this thesis aims to critically analyse the effectiveness of the legal remedies available to spouses who are negatively affected by the dissipation of marital assets in marriage in community of property and marriage out of community of property with accrual. In this thesis the question is asked: does the current law adequately protect one spouse from another spouse unfairly hiding or dissipating assets from their estate to prevent the equitable distribution of these assets to the other spouse on divorce? In order to answer this question, this thesis proceeds by examining each of the remedies in detail, looking specifically at the statutory remedies set out in the Matrimonial Property Act 88 of 1984, specifically those contained in ss 8, 15 and 20 of that Act. It also considers remedies found in the common law. Ultimately, the study finds that these remedies do not provide adequate protection to spouses affected by the dissipation of marital assets and looks at the particular reasons for this finding. The study then concludes by proposing reforms to provide better protection to affected spouses. These legal reforms include: amending the legislative framework, changing the determinative date of the accrual, legislating a requirement for full disclosure of assets in terms s 8(1) of the Matrimonial Property Act and, finally, advocating for a flexible interpretation of the requirements of s 20 of the Matrimonial Property Act and the common law anti-dissipation remedy.
Keywords: Marital property -- South Africa; Equitable distribution of marital property -- South Africa; Divorce Economic aspects -- South Africa; Community property -- South Africa; Hidden asset; Divorce settlements -- South Africa